Weak Solutions for Nonlinear Fractional Differential Equations in Banach Spaces - Wen-Xue Zhou; Ying-Xiang Chang; Hai-Zhong Liu (Discrete Dynamics in Nature and Society)
We discuss the existence of weak solutions for a nonlinear boundary value problem of fractional differential equations in Banach space. Our analysis relies on the Mönch's fixed point theorem combined with the technique of measures of weak noncompactness.